Utility of synthetic MRI in predicting the Ki-67 status of oestrogen receptor-positive breast cancer: a feasibility study. Issue 5 (May 2020) - Matsuda, M.; Kido, T.; Tsuda, T.; Okada, K.; Shiraishi, Y.; Suekuni, H.; Kamei, Y.; Kitazawa, R.; Mochizuki, T.
Abstract : AIM: To evaluate the utility of synthetic magnetic resonance imaging (MRI) of the breast in predicting the Ki-67 status in patients with oestrogen receptor (ER)-positive breast cancer. MATERIALS AND METHODS: Forty-nine patients with 50 histopathologically proven breast cancers who underwent additional synthetic MRI were enrolled in the present study. Using synthetic MRI images, T1 and T2 relaxation times and their standard deviations (SD) in the breast lesions before (T1-Pre, T2-Pre, PD-Pre, SD of T1-Pre, SD of T2-Pre, SD of PD-Pre) and after (T1-Gd, T2-Gd, PD-Gd, SD of T1-Gd, SD of T2-Gd, SD of PD-Gd) contrast agent injection were obtained. These quantitative values were compared between the low Ki-67 expression (<14%) lesions (low-proliferation group: n= 23) and high Ki-67 expression (≥14%) lesions (high-proliferation group: n= 27). RESULTS: The univariate analysis showed that the SD of T1-Gd ( p< 0.001) and T2-Gd ( p= 0.042) were significantly higher in the high-proliferation group than in the low-proliferation group. Multivariate analysis further showed that the SD of T1-Gd was a significant and independent predictor of Ki-67 expression, with an area under the receiver operating characteristic (AUROC) curve of 0.885. The sensitivity, specificity, and accuracy of the SD of T1-Gd with an optimal cut-off value of 98.5 were 77.8%, 87%, and 82%, respectively. CONCLUSION: The SD of T1-Gd obtained from synthetic MRI was useful to predict Ki-67 status.